2004
DOI: 10.1017/s1355617704107054
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impulsivity and HIV serostatus in substance dependent males

Abstract: HIV-seropositive (HIV+) drug users show impaired performance on measures of integrity of prefrontal–subcortical systems. The Iowa Gambling Task (GT) is mediated primarily through ventromedial–prefrontal systems, and poor performance on this measure (“cognitive impulsivity”) is common among substance dependent individuals (SDIs) as well as patients with disease involving prefrontal–subcortical systems (e.g., Huntington disease). We hypothesized that HIV+ SDIs might be more vulnerable to cognitive impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
87
4
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 35 publications
13
87
4
2
Order By: Relevance
“…Although both depression and anxiety were included in the psychi-atric index of the ASI, and therefore we controlled for these variables in the regression models, further research using specific measures for these and other co-morbid conditions will be required to fully determine their role and influence. Furthermore, decision-making as measured by the IGT requires multiple cognitive and emotional mechanisms brought together Crone et al, 2004;Maia & McLelland, 2004;Martin et al, 2004). Thus, impairments of SDIs in working memory, response inhibition, or rule detection may equally play an influential role in modulating the relationships between a number of real-life aspects associated with severity of addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both depression and anxiety were included in the psychi-atric index of the ASI, and therefore we controlled for these variables in the regression models, further research using specific measures for these and other co-morbid conditions will be required to fully determine their role and influence. Furthermore, decision-making as measured by the IGT requires multiple cognitive and emotional mechanisms brought together Crone et al, 2004;Maia & McLelland, 2004;Martin et al, 2004). Thus, impairments of SDIs in working memory, response inhibition, or rule detection may equally play an influential role in modulating the relationships between a number of real-life aspects associated with severity of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the IGT is a multidetermined task requiring a variety of cognitive and emotional functions, including affective processing of ongoing somatic feedback (Bechara & Damasio, 2002;Crone et al, 2004), working memory, response inhibition, planning, and rule detection Maia & McLelland, 2004;Martin et al, 2004). Therefore, decision-making as measured by the IGT involves multiple candidate mechanisms in which SDIs are frequently impaired.…”
Section: Introductionmentioning
confidence: 99%
“…A 12-session version of the therapy-3-S ϩ -which is the focus of the current report, has also been developed for HIV-positive drug users. The need for a version of the therapy specifically for drug users living with HIV/AIDS was based not only on the potential for higher levels of impulsivity in this patient population (Martin et al, 2004), but also on prior research suggesting that a high percentage of HIV-positive drug users continue to engage in behaviors that transmit HIV to others, and that may contribute to "superinfection" of the already infected individual (Avants, Warburton, Hawkins, & Margolin, 2000). They are also at increased risk for nonadherence to life-sustaining medical regimens (Avants, Margolin, Warburton, Hawkins, & Shi, 2001).…”
mentioning
confidence: 99%
“…A number of studies have found that bilateral lesions of the ventromedial prefrontal lobe (VM) are associated with poor (i.e., risky) performance (Bechara, Damasio, Damasio, & Lee, 1999;Bechara, Damasio, Tranel, & Anderson, 1998;Bechara, Tranel, & Damasio, 2000), while left-sided lesions do not affect performance (Manes et al, 2002). From these studies, it appears that such lesions result in a decision-making that is based on immediate gratification with little concern for future outcome.Research into the decision-making characteristics of substance abusers (Grant, Contoreggi, & London, 2000), including HIV-infected substance abusers (Martin et al, 2004), has also employed the gambling task. Substance abusers and VM individuals often overlap in real-life behaviors in which they opt for choices that result in immediate reward despite the potential for negative consequences, and this observation has been replicated with the gambling task (Bechara et al, 2001;Bechara, Dolan, & Hindes, 2002;Bechara & Damasio, 2002).…”
mentioning
confidence: 99%